PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INSTRUKSIONAL INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS X PADA MATERI KESEIMBANGAN PASAR - Silvia Marfiatus Sholihah; Muhammad Abdul Ghofur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Economics learning has a strategic role in helping students understand how the economic system works, one of which is through the material on market equilibrium which is an important part of economics learning at the senior high school level. However, this material is quite complex because it is abstract and requires analytical skills on the relationship between demand and supply visualized through a curve. The phenomenon of students' difficulty in understanding the concept of market equilibrium is seen in SMAS IPIEMS Surabaya, where 58% of students stated that the material on market equilibrium is difficult and 31% of students have not achieved the Learning Objective Achievement Criteria (KKTP). This condition indicates that students' conceptual understanding of the material on market equilibrium is still low so that learning objectives have not been achieved optimally. This study aims to develop interactive instructional video learning media to improve the understanding of grade X students on the material on market equilibrium, describe the feasibility of the developed learning media, and determine the success of the media in improving student understanding. The development model used is the ADDIE model which consists of five stages, namely: Analysis, Design, Development, Implementation, Evaluation. The results of this study indicate that interactive instructional video learning media on the material on market equilibrium is feasible to use. Validation results showed a feasibility percentage of 86.66% from material experts, categorized as very good, 78.9% from media experts, categorized as good, and 80% from language experts, categorized as good. Furthermore, limited trial results indicated that interactive instructional video learning media can improve student understanding.